An Idiosyncratic Ethics, Or, the Lauramachean Ethics - Miller, George David (Value Inquiry Book Series, 1994)
This book is an original synthesis of four elements: (1) the phenomenology of value, (2) caring, (3) the moral imagination, and (4) Kant's formula of humanity. The striking result is an ethics of caring that develops our shared humanity. The probing analysis and pungent argument are assisted by imaginative forms of dialogue, narration, and parable. This lively contribution to our ethical fulfillment concludes with a case for student-centered education that is democratic, creative and caring.